Why Firing Rate Distributions Are Important for Understanding Spinal Central Pattern Generators - Lindén, Henrik; Berg, Rune W. (Frontiers in Human Neuroscience, 2021)
Networks in the spinal cord, which are responsible for the generation of rhythmic movements, commonly known as central pattern generators (CPG), have remained elusive for decades. Although it is well-known that many spinal neurons are rhythmically active, little attention has been given to their firing rates. Nevertheless, here we argue that the distribution of firing rates across the population can provide a crucial clue to the organization of the CPGs. In fact, the shape of the distribution critically cast doubt on the widespread idea of a modular division, in which populations of excitatory neurons reciprocally connected by inhibitory populations. We test models of recurrently connected excitatory networks and show that the population would quickly reach the maximum firing rates thus equalizing the spiking activity across the population. The population distribution of firing rates hence consists of a narrow peak near the maximum. Nevertheless, this is incompatible with experiments, that show wide lognormal-like distributions and a peak close to zero. As an alternative, we suggest central feedback inhibition.